Effect of Exchange Rate on Stock Price Movement in Nigeria - Anthony O. Adaramola; Mojisola A. Abere; Omoruyi Fidelis Ogiamien (Financial Markets, Institutions and Risks)
Theories of exchange rate in developing economies suggest that between exchange rate and stock price movement, a positive relationship exists. In Nigeria, depreciation of local currency to many seems not to have brought about the expected increase in export or output in the industrial sector, let alone the firms’ stock prices. This study was therefore set out to investigate the effect that exchange rate has on stock price movement in Nigeria and the direction of causality between the two. Data on exchange rate, interest rate, inflation rate, gross domestic product and stock market index in Nigeria were used for the analyses. Auto Regressive Distributed Lag (ARDL) test was used to assess the possibility of existence of a long run association between exchange rate and stock price movement. Results established a long run and significant relationship between exchange rate and stock price movement in Nigeria (F:12.89 >Io & I1Bound, P-value < 0.05 for LEXR, LGDP LINF). However, the negative coefficients of the regressors; especially exchange rate, run contrary to existing theories on the benefits of depreciating exchange rates. This means that Nigeria has not fully reaped the expected benefits from devaluation of her local currency over the years. A unidirectional causality between exchange rate and stock price movement was also discovered. Causation flows from exchange to stock price (P-value < 0.05 for LEXR). This further suggests that most firms in Nigeria lack the absorption capacity to transform the accruing gains of currency depreciation to increased productivity and exports.